Hemifacial Spasm: Comparison of Results between Patients Older and Younger than 70 Years Operated on with Microvascular Decompression - Zhao, Hua; Zhu, Jin; Tang, Yin-da; Shen, Lin; Li, Shi-ting (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objective The aim of the present study was to evaluate the efficacy and safety of microvascular decompression (MVD) for primary hemifacial spasm (HFS) in patients aged ≥70 years and to compare the outcome with a control cohort of younger patients(<70 years).Methods In this retrospective study, subjects were divided into two groups: an elderly group (patients who were ≥70 years) and a younger group. We compared demographic and clinical data, surgical outcome, MVD-related complications, and duration of operation and hospitalization after MVD between the two groups.Results At a mean follow-up of 32 ± 4.2 months, 188 elderly patients (90.4%) reported an effective outcome without need for any medication versus 379 (91.1%) of the younger cohort. There was no mortality in both cohorts. The prevalence of delayed facial palsy was 4.8% in the elderly group and 4.1% in the younger group. One (0.5%) patient in the elderly group and 3 (0.7%) patients in the younger group suffered cerebrospinal fluid (CSF) leakage. There was no significant difference between the two groups in terms of MVD-related complications, such as delayed facial palsy, hearing impairment, CSF leakage, and hematoma.Conclusions MVD is an effective treatment option in elderly patients with HFS as well as in younger patients. Age itself seems to be no relevant contraindication or, alternatively, risk factor regarding MVD.
Keywords: efficacy; elderly; hemifacial spasm; microvascular decompression; safety